2010
DOI: 10.1038/cddis.2010.62
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of human FasL modulates its cell death-inducing function

Abstract: Fas ligand (FasL) is a transmembrane protein that regulates cell death in Fas-bearing cells. FasL-mediated cell death is essential for immune system homeostasis and the elimination of viral or transformed cells. Because of its potent cytotoxic activity, FasL expression at the cell surface is tightly regulated, for example, via processing by ADAM10 and SPPL2a generating soluble FasL and the intracellular fragments APL (ADAM10-processed FasL form) and SPA (SPPL2a-processed APL). In this study, we report that Fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 39 publications
1
33
0
2
Order By: Relevance
“…S-acylation of the neurotensin receptor 1 (NTSR-1), a key mediator in breast, pancreas, prostate, colon and lung cancers, is essential for its localization and efficient signaling (Heakal et al, 2011). The induction of apoptosis is an efficient way to stop tumor development, many proteins involved in apoptosis are S-acylated including FasL (Fas Ligand; Guardiola-Serrano et al, 2010), FasR (Fas receptor; Chakrabandhu et al, 2007), DR4 (a receptor of the tumor necrosis factor-related apoptosis-inducing ligand; Rossin et al, 2009), DCC (deleted in colorectal cancer; Furne et al, 2006), UNC5H (Maisse et al, 2008) and BAX (BCL-2-associated X) (Fröhlich et al, 2014). The spread of cancer cells from their original site to other parts of the body is through metastasis.…”
Section: S-acylationmentioning
confidence: 99%
“…S-acylation of the neurotensin receptor 1 (NTSR-1), a key mediator in breast, pancreas, prostate, colon and lung cancers, is essential for its localization and efficient signaling (Heakal et al, 2011). The induction of apoptosis is an efficient way to stop tumor development, many proteins involved in apoptosis are S-acylated including FasL (Fas Ligand; Guardiola-Serrano et al, 2010), FasR (Fas receptor; Chakrabandhu et al, 2007), DR4 (a receptor of the tumor necrosis factor-related apoptosis-inducing ligand; Rossin et al, 2009), DCC (deleted in colorectal cancer; Furne et al, 2006), UNC5H (Maisse et al, 2008) and BAX (BCL-2-associated X) (Fröhlich et al, 2014). The spread of cancer cells from their original site to other parts of the body is through metastasis.…”
Section: S-acylationmentioning
confidence: 99%
“…6,7 We demonstrated that Fas and FasL are constitutively modified by S-palmitoylation, a reversible post-translational modification that consists in the addition of a palmitic acid on the cysteine residue through a thiol linkage. [8][9][10] The palmitoylation of a protein can affect its interactions with its surrounding membrane lipids and proteins, therefore impacting certain properties such as association with specific membrane domains, trafficking between cell compartments or stability. [11][12][13] The palmitoylation reaction is catalyzed by the conserved DHHC (aspartate-histidine-histidine-cysteine) family of enzymes, which are characterized by the specific DHHC motif required for the palmitoyl acyltransferase (PAT) activity.…”
mentioning
confidence: 99%
“…The palmitoylation on Cys plays roles in protein trafficking and proteineprotein interactions. Although it was unclear whether RANKL can be palmitoylated, it had been shown that the Cys in FasL, which is one member of TNF super family like RANKL, was palmitoylated [30]. Current efforts focus on the posttranslational modification especially palmitoylation on Cys amino acids of RANKL in an attempt to gain further insight into the mechanisms for the formation of Arl6ip5-RANKL complex and the regulation of RANKL intracellular trafficking.…”
Section: Discussionmentioning
confidence: 99%